Audience Responses and Gendered Paratexts in Film Title Translation: Evidence from Chinese Social Media - Tian, Xiaoming; Gao, Xuduo; Wu, Fei (Cultural Conflict and Integration, 2026)
This study investigates translated film titles as ideological sites in contemporary Chinese media discourse, where gender identities are erased, objectified, misrepresented, or reclaimed. It examines how such paratextual choices trigger cultural conflict and negotiation during cross-cultural circulation. Guided by paratext theory and feminist approaches to media discourse, this study employs thematic analysis to examine how institutional translation strategies and networked audience responses jointly shape gendered meanings in translated film titles. Drawing on over 400 user-generated commentaries from three major Chinese social media platforms, Weibo (Microblog), Xiaohongshu (Red Note), and Douyin (TikTok), this study identifies four dominant patterns in public responses to film title translation. First, some translations erase feminine subjectivity through lexical omission. Second, some translations reduce female characters to objects of desire by employing sexualized or aestheticized language. Third, even when women are visible, their presence is frequently reframed within heteronormative or romanticized tropes that distort or dilute the original film’s feminist or gender-critical intent. Finally, networked audiences mobilize discursive resistance by offering ironic commentary and alternative translations that foreground feminist agency and media literacy, thereby articulating vernacular strategies of cultural integration and mutual intelligibility. These findings challenge the conventional view of translation as a neutral transfer. Instead, they highlight translation’s role as a publicly contested cultural act, shaped by social scrutiny and identity politics. This has important implications for intercultural communication and the management of cultural differences. The study advocates for increased attention to gendered representation in paratextual translation and supports participatory models that integrate audience feedback as a pathway to more inclusive and equitable cross-cultural narratives.